2006
DOI: 10.1088/0022-3727/39/11/009
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying the density of a horizontal electric field to improve light efficiency in a fringe-field switching liquid crystal display

Abstract: The transmittance in fringe-field switching liquid crystal (LC) displays, which show a wide viewing angle, is dependent on the position along the electrode position. The reason for this is that the dielectric torque (and hence the twist angle) varies with position. This effect depends on the type of LC: a display using an LC with positive dielectric anisotropy has less transmittance than one with negative dielectric anisotropy. Furthermore, the transmittance decreases with decreasing cell gap. The difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 11 publications
0
32
0
2
Order By: Relevance
“…If a +LC with IPS mode concepts will be used, however, the transmittance of the FFS-LCD will no longer be excellent, and a certain level of pooling mura will appear. At that time, there were extensive studies regarding what determines the transmittance of the FFS-LCD with +LC, and it was found that the light efficiency of the LC mode was dependent on many cell parameters, such as the LC's retardation [16], the cell gap [17], the electrode structure [18], and the magnitude of dielectric anisotropy [19]. In addition, it is widely known that the transmittance of the LCD is dependent not only on the LC's light efficiency but also on the pixel aperture ratio.…”
Section: Second Development Stage Of the Ffs Modementioning
confidence: 99%
“…If a +LC with IPS mode concepts will be used, however, the transmittance of the FFS-LCD will no longer be excellent, and a certain level of pooling mura will appear. At that time, there were extensive studies regarding what determines the transmittance of the FFS-LCD with +LC, and it was found that the light efficiency of the LC mode was dependent on many cell parameters, such as the LC's retardation [16], the cell gap [17], the electrode structure [18], and the magnitude of dielectric anisotropy [19]. In addition, it is widely known that the transmittance of the LCD is dependent not only on the LC's light efficiency but also on the pixel aperture ratio.…”
Section: Second Development Stage Of the Ffs Modementioning
confidence: 99%
“…FFS모드 에서 투과율은 셀갭이 4㎛에서 3㎛로 감소시 투과율이 감소 하게 되는데 이는 역시 셀갭이 감소시 탄성토크에 의한 A지 점의 투과율 감소 영향과 더불어 전극 위치에 따른 투과율을 극대화는 전압이 다르기 때문이다 [28,29] . 이러한 단점은 가능 한 전극폭을 약 2㎛로 줄이고 간격을 3~4㎛정도 가져가면 탄성토크 영역이 최소화하며 투과율이 극대화된다 [18,30,31] . 이 러한 이유로 현재 고정세 FFS제품은 전극 폭이 3㎛ 이하로 예상된다.…”
Section: Ffs모드에서 전극 위치에 따른 광변조unclassified
“…One interesting feature of the FFS device is that the twist angle of the LC in on state is strongly dependent on the electrode position due to different field intensity along the electrode position. Hence the twist angle is highest at the edge of pixel electrode and lowest at the center of pixel electrode [16].…”
Section: Introductionmentioning
confidence: 95%